“E-exhibition" a framework of students' project based learning - Oktavia Widiastuti (Jurnal Linguistik Terapan, 2016)
Project-based learning (PBL) hails from a tradition of pedagogy which asserts that students learn best by experiencing and solving real-world problems. Studies have proven that when implemented well, project-based learning results positive outcomes related to students’ learning in the areas of content knowledge, collaborative skills, engagement and motivation, and critical thinking and problem-solving skills. E-Exhibition “English Entrepreneur and Entertainment Exhibition” is chosen as a framework of students’ project based learning. The main focus of this exhibition is to assess students’ performance and progress through project as a practical and meaningful way of learning. This exhibition represents a multi-faceted assessment. Students get multiple opportunities by feedback and revise works, students receive multiple learning outcomes in term of problem-solving, content, and collaboration, students presentation in the exhibition encourage their communicative and social value skills.